2006
DOI: 10.1111/j.1477-9730.2006.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

A geometric model for linear‐array‐based terrestrial panoramic cameras

Abstract: Digital panoramic cameras represent a powerful tool for generating high resolution images of scenes. They generate images of up to 100 000 · 10 000 pixels and are especially suited for 360°recording of objects such as indoor scenes or city squares. The paper describes the development of a strict geometric model for rotating linear array panoramic cameras and the extension of the model by additional parameters adapting the camera model to the physical reality. The camera model has been implemented in a spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 1 publication
0
46
0
Order By: Relevance
“…The model allows 3D object space points to be projected into image space and the inverse of this operation, i.e., the creation of 3D object space rays emanating from the camera, for any desired image pixel. To date, most of the terrestrial HSI applied to geologic studies has been collected with panoramic linear array sensors that rotate around a vertical axis intersecting the camera optical centerline, thus forming a standard cylindrical model [5,24]. However, the optical centerline of the SWIR camera used in this work is offset from the stage rotation axis by approximately 20 cm due to the simultaneous presence of both the VNIR and SWIR cameras on the stage (see Figure 2).…”
Section: Hsimentioning
confidence: 99%
“…The model allows 3D object space points to be projected into image space and the inverse of this operation, i.e., the creation of 3D object space rays emanating from the camera, for any desired image pixel. To date, most of the terrestrial HSI applied to geologic studies has been collected with panoramic linear array sensors that rotate around a vertical axis intersecting the camera optical centerline, thus forming a standard cylindrical model [5,24]. However, the optical centerline of the SWIR camera used in this work is offset from the stage rotation axis by approximately 20 cm due to the simultaneous presence of both the VNIR and SWIR cameras on the stage (see Figure 2).…”
Section: Hsimentioning
confidence: 99%
“…Because rotation is required to build up the number of image columns, the width of an image is variable, determined by the user. This configuration results in panoramic imaging geometry, where only the across-track image direction can be represented by central perspective projection (Luhmann et al, 2006;Schneider and Maas, 2006). Spatial resolution is low compared with a contemporary digital camera, but the high spectral resolution allows greater differentiation of mineral content.…”
Section: Instrumentation and Data Collectionmentioning
confidence: 99%
“…Previous work (Kurz et al, 2011) has shown that the geometric model for the HySpex sensor can be represented by a standard model for linear-array panoramic cameras (Schneider and Maas, 2006). Additional parameters defined in this model account for the horizontal pixel size defined by the rotation step, and the non-parallelism of the sensor line and rotation axis.…”
Section: Processingmentioning
confidence: 99%
“…Many hyperspectral imagers operate as pushbroom line sensors mounted on a rotation stage. These cameras have to be modelled as panorama cameras with cylindrical image geometry for photogrammetric processing (Schneider and Maas 2006), in contrast to conventional frame cameras. Hyperspectral imagery is registered to the lidar coordinate system measuring ground control points within an image either manually or in an automatic manner (Monteiro et al 2013, Sima et al 2014.…”
Section: Integration With Topographic Datamentioning
confidence: 99%